PEMANFAATAN GADAI PERKEBUNAN DI DESA AIR BULUH KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - alek saputra (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2020)
Utilization of Pawning goods in the form of gardens that creates uncertainty in terms of right and obligation. So it is often a problem in the midst of society and obstacles in its implementation. As is the case in Air Buluh Village, Kuantan Mudik District, Kuantan Singingi Regency